Readiness to Provide Medications for Addiction Treatment in HIV Clinics: A Multisite Mixed-Methods Formative Evaluation. (1st July 2021) - Edelman, E. Jennifer; Gan, Geliang; Dziura, James; Esserman, Denise; Morford, Kenneth L.; Porter, Elizabeth; Chan, Philip A.; Cornman, Deborah H.; Oldfield, Benjamin J.; Yager, Jessica E.; Muvvala, Srinivas B.; Fiellin, David A.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: We sought to characterize readiness, barriers to, and facilitators of providing medications for addiction treatment (MAT) in HIV clinics. Setting: Four HIV clinics in the northeastern United States. Methods: Mixed-methods formative evaluation conducted June 2017–February 2019. Surveys assessed readiness [visual analog scale, less ready (0–<7) vs. more ready (≥7–10)]; evidence and context ratings for MAT provision; and preferred addiction treatment model. A subset (n = 37) participated in focus groups. Results: Among 71 survey respondents (48% prescribers), the proportion more ready to provide addiction treatment medications varied across substances [tobacco (76%), opioid (61%), and alcohol (49%) treatment medications ( P values < 0.05)]. Evidence subscale scores were higher for those more ready to provide tobacco [median (interquartile range) = 4.0 (4.0, 5.0) vs. 4.0 (3.0, 4.0), P = 0.008] treatment medications, but not significantly different for opioid [5.0 (4.0, 5.0) vs. 4.0 (4.0, 5.0), P = 0.11] and alcohol [4.0 (3.0, 5.0) vs. 4.0 (3.0, 4.0), P = 0.42] treatment medications. Median context subscale scores ranged from 3.3 to 4.0 and generally did not vary by readiness status ( P values > 0.05). Most favored integrating MAT into HIV care but preferred models differed across substances. Barriers to MAT included identification of treatment-eligible patients, variable experiences with MAT and perceived medication complexity, perceived need for robust behavioral services, and inconsistent availability of on-site specialists. Facilitators included knowledge of adverse health consequences of opioid and tobacco use, local champions, focus on quality improvement, and multidisciplinary teamwork. Conclusions: Efforts to implement MAT in HIV clinics should address both gaps in perspectives regarding the evidence for MAT and contextual factors and may require substance-specific models.